Community Volunteers Monitor Water System Security. Issue 8 (1st August 2015) - Stephens, Scott; Haynie, Linda
Abstract : Homeland security for critical infrastructure is a shared responsibility, requiring coordinated action among federal, state, and local governments; the private sector; and concerned citizens. The Austin Water Utility (AWU) and Austin Office of Homeland Security and Emergency Management help advance infrastructure and community security and resilience by partnering with and training community volunteers for disaster preparedness and monitoring key water assets.